Procession passing through traditional East Indian homes - Mumbai Archive Project Team (Jio Institute, 2024)
The procession passes along Dongri Road, passing old-style bungalows. Traditional East Indian houses feature tiled roofs, which help keep the interiors cool during hot summer months. They also have large verandas or porches that serve as spaces for socializing.